Scaling-up of a novel, simplified MFC stack based on a self-stratifying urine column. Issue 1 (December 2016) - Walter, Xavier; Gajda, Iwona; Forbes, Samuel; Winfield, Jonathan; Greenman, John; Ieropoulos, Ioannis
Abstract Background The microbial fuel cell (MFC) is a technology in which microorganisms employ an electrode (anode) as a solid electron acceptor for anaerobic respiration. This results in direct transformation of chemical energy into electrical energy, which in essence, renders organic wastewater into fuel. Amongst the various types of organic waste, urine is particularly interesting since it is the source of 75 % of the nitrogen present in domestic wastewater despite only accounting for 1 % of the total volume. However, there is a persistent problem for efficient MFC scale-up, since the higher the surface area of electrode to volume ratio, the higher the volumetric power density. Hence, to reach usable power levels for practical applications, a plurality of MFC units could be connected together to produce higher voltage and current outputs; this can be done by combinations of series/parallel connections implemented both horizontally and vertically as a stack. This plurality implies that the units have a simple design for the whole system to be cost-effective. The goal of this work was to address the built configuration of these multiple MFCs into stacks used for treating human urine. Results We report a novel, membraneless stack design using ceramic plates, with fully submerged anodes and partially submerged cathodes in the same urine solution. The cathodes covered the top of each ceramic plate whilst the anodes, were on the lower half of each plate, and this would constitute a module. The MFC elements within each module (anode, ceramic, and cathode) were connected in parallel, and the different modules connected in series. This allowed for the self-stratification of the collective environment (urine column) under the natural activity of the microbial consortia thriving in the system. Two different module sizes were investigated, where one module (or box) had a footprint of 900 mL and a larger module (or box) had a footprint of 5000 mL. This scaling-up increased power but did not negatively affect power density (≈12 W/m3 ), a factor that has proven to be an obstacle in previous studies. Conclusion The scaling-up approach, with limited power-density losses, was achieved by maintaining a plurality of microenvironments within the module, and resulted in a simple and robust system fuelled by urine. This scaling-up approach, within the tested range, was successful in converting chemical energy in urine into electricity.